Revisión bibliográfica de los métodos del comportamiento canino (2021)
The bond that has been generated between humans and dogs has managed to create a relationship of mutual coexistence, whether with mixed-breed or pure-breed canines. Hence the need to carry out a bibliographic review of the different diagnostic methods of canine behavior, which allow the assessment of inappropriate behaviors that dogs have. For the development of this work, all scientific articles on canine behavior diagnosis methods published since 2010 were used as a universe, and as a sample, 14 research papers published in journals, web portals, databases and national scientific dissemination portals were taken as a sample. foreign. Works published between 2010 and 2020 were prioritized. The work was descriptive and as a result, the design of several methods to diagnose canine behavior was found: C-barq, Safer, initial assessment of the behavior of dogs in a collection center and evaluation of the behavior of puppies during the first consultation clinic. The questionnaires allow the centers to evaluate dimensions of social behavior and the evaluation tests are used mainly for the selection of working animals.